Synthesis and characterisation of zinc oxide nanoparticles and its antimicrobial activity against Staphylococcus aureus and Micrococcus. (28th July 2021) - Kaur, Gagandeep; Sondhi, Sonica; Kaur, Palki Sahib; Kamboj, Anjoo; Verma, Shalini
A detailed analysis of synthesis and characterisation of zinc oxide (ZnO) nanoparticles (NPs) with a motive of demonstrating the effect of ZnO on its antibacterial effect is reported herein. A rapid synthesis method of highly dispersed ZnO nanoparticles by using zinc acetate dihydrate and ammonium carbonate as a precursor and polyethylene glycol (PEG) as a capping agent is presented in this study. The results of characterisation techniques like ultraviolet visible (UV-Vis) spectroscopy, zeta potential and particle size analyser confirmed ZnO NPs of better quality and of uniform sized. Further, the ZnO NPs revealed promising inhibitory activity against the growth of Staphylococcus aureus and Micrococcus .